Halotolerant and plant growth-promoting endophytic fungus Aspergillus terreus CR7 alleviates salt stress and exhibits genoprotective effect in Vigna radiata - Chauhan, Pooja; Singh, Mandeep; Sharma, Avinash; Singh, Mangaljeet; Chadha, Pooja; Kaur, Amarjeet (Frontiers in Microbiology, 2024)
Soil salinity is one of the major environmental stresses that results in reduction of cultivable land and decreased productivity. In the present study, halotolerant and plant growth-promoting endophytic fungi were isolated from Catharanthus roseus and their effect in mitigating salt stress in Vigna radiata was evaluated. An isolate CR7, identified to be Aspergillus terreus, showing plant growth promotion activities, viz. IAA production (23.43 ± 0.79 µg/ml), phosphate solubilization (133.63 ± 6.40 µg/ml), ACC deaminase activity (86.36 ± 2.70 µmol α-ketobutyrate/h/mg protein) etc. and ability to grow at 15% NaCl was selected for further in vivo studies. Colonization of CR7 was carried out in Vigna radiata which was subjected to different concentrations of salt (150mM, 200mM, 250mM NaCl). Under salt stress, A. terreus CR7 inoculated plants showed substantially improved root and shoot length, biomass, chlorophyll content, relative water content, phenolics, protein content and DPPH scavenging activity. Endogenous IAA level was enhanced by 5.28 fold in treated plants at maximum salt stress. Inoculation of A. terreus CR7 affected oxidative stress parameters, exhibiting an increase in catalase and superoxide dismutase and reduction in proline, electrolyte leakage and malondialdehyde content. Fluorescent microscopic analysis of roots revealed improved cell viability and decreased levels of glutathione and hydrogen peroxide under salt stress in treated plants. The isolate A. terreus CR7 also protected against DNA damage induced by salt stress which was evaluated using comet assay. A decrease in DNA tail length, tail moment and olive tail moment to the extent of 19.87%, 19.76% and 24.81%, respectively, was observed in A. terreus CR7 colonized plants under salt stress. It can be concluded that A. terreus CR7 can be exploited for alleviating the impact of salt stress in crop plants.